2021
DOI: 10.3389/finsc.2021.685755
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Effects of Conventional and Organic Insecticides on the Parasitoid Trissolcus japonicus, a Biological Control Agent for Halyomorpha halys

Abstract: The egg parasitoid Trissolcus japonicus is a natural enemy of Halyomorpha halys, a polyphagous invasive pest in Europe and North and South America. Integration of chemical and biological control tactics could facilitate effective and sustainable integrated pest management programs. This study was conducted to assess (i) the lethal effects of field rates, (ii) the sublethal effects of maximum and half field rates, and (iii) the lethal effects of different routes of exposure of three organic and two conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Our experiments demonstrated that pyrethrin was toxic to T. radiata, and its residual effects on the parasitoid persisted for 3 days following the exposure, resulting in significant mortality and reduced parasitism rate compared to control. The negative effects of pyrethrum have also been shown for other parasitoids, such as Trissolcus japonicus (Ashmead), Anastatus reduviid (Howard), and Chelonus oculator Panzer (Cem et al, 2014;Ogburn & Walgenbach, 2019;Ribeiro et al, 2021). The lethal and sublethal effects of pyrethrum on natural enemies suggest that it must be used with caution even though it is a natural pesticide.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments demonstrated that pyrethrin was toxic to T. radiata, and its residual effects on the parasitoid persisted for 3 days following the exposure, resulting in significant mortality and reduced parasitism rate compared to control. The negative effects of pyrethrum have also been shown for other parasitoids, such as Trissolcus japonicus (Ashmead), Anastatus reduviid (Howard), and Chelonus oculator Panzer (Cem et al, 2014;Ogburn & Walgenbach, 2019;Ribeiro et al, 2021). The lethal and sublethal effects of pyrethrum on natural enemies suggest that it must be used with caution even though it is a natural pesticide.…”
Section: Discussionmentioning
confidence: 99%
“…The 2019 early season tree canopy application with pyrethrin did not have a visible impact on beneficial insects. Pyrethrin has been shown to cause deleterious effects on natural enemies such as stink bug egg parasitoids but seems to be less harmful than another organic insecticide, Spinosad (Ogburn and Walgenbach 2019;Ribeiro et al 2021). This mixed response of predators and parasitoids could be influenced by pyrethrin's low persistence and its repellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrethrins have certain advantages as IPM tools such as their low toxicity to mammals, birds, and beneficial insects, such as predators and pollinators [198][199][200][201][202][203], and their short environmental persistence as they break down quickly in sunlight and air, leaving no residues [203,204]. However, pyrethrins also have some limitations and challenges such as reductions in longevity and fecundity in certain parasitoids [205], a repellent effect in some insects [206], and the emergence of resistance [207][208][209][210]. Depending on the active ingredients and target insects, botanical insecticides work in a variety of ways.…”
Section: Biopesticides and Inert Materials In Ipmmentioning
confidence: 99%